SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PEMASOK MESIN INDUSTRI MENGGUNAKAN METODE ELECTRE (ELIMINATION ET CHOIX TRADUISANT LA REALITE) - Ade Suryanto (LPPM Universitas Abdurrab, 2022)
The current industry will not escape the role of suppliers to support their needs, especially the provision of consumptive products. The company cooperates not only with one partner or supplier, but to provide satisfaction to customers with the variety of products sold and from the price of the products offered, the company establishes relationships with many partners or suppliers. Currently in the selection process the selection of partners is still carried out in a simple manner, as long as partners can still send the required products, they are considered capable and worthy to be business partners. This study wants to prove and test the feasibility of several partners or alternatives using the Electre method. The criteria include delivery time, production capacity, discounted prices, payment terms and quality of goods. The partners or suppliers are manufacturers of industrial machines that have products with similar functions, only slightly different in features and product brands. The number of data tested was 5 partners to compare the feasibility level. The method used is by using the ELECTRE (Elimination Et Choix Traduisant La Reality) method, the stages include Normalizing the Decision Matrix, Weighting the Normalized Matrix, Determining the Concordance and Discordance Sets on the Index, Calculating Concordance and Discordance Matrices, Calculating the Concordance Dominant Matrix and Discordance, Determining the Aggregate Dominance Matrix and Elimination of Less Favorable Alternatives. The final results obtained from the 5 alternatives tested showed that alternatives A1, A2, and A5, were alternatives that were considered feasible to be made permanent partners as product suppliers to the company.